2018
DOI: 10.1111/dom.13598
|View full text |Cite
|
Sign up to set email alerts
|

A head‐to‐head comparison of personal and professional continuous glucose monitoring systems in people with type 1 diabetes: Hypoglycaemia remains the weak spot

Abstract: To compare the performance of a professional continuous glucose monitoring (proCGM) and a personal continuous glucose monitoring (persCGM) system worn in parallel under standardized conditions in individuals with type 1 diabetes (T1D), two CGM systems (iPro2 – proCGM; Minimed 640G – persCGM) worn in parallel using the same sensor (Enlite 2) were compared. Ten people with T1D were included in this single‐centre, open‐label study in which CGM performance was evaluated. The study consisted of a 24‐hours inpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 21 publications
6
16
1
Order By: Relevance
“…This is contrary to the findings of Aberer et al, who identified a mean absolute relative difference of 14.6% with the flash GM system . When comparing findings of our study to those concerning other CGM devices (iPro2, Enlite 2 and Minimed 640G, Medtronic), it appears that hypoglycaemia might be a challenge to the flash GM system . Additionally, during acute exercise accompanied by hypoglycaemia, flash GM data indicated a MARD of 45.1%; hence, glucose values must be interpreted very cautiously.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is contrary to the findings of Aberer et al, who identified a mean absolute relative difference of 14.6% with the flash GM system . When comparing findings of our study to those concerning other CGM devices (iPro2, Enlite 2 and Minimed 640G, Medtronic), it appears that hypoglycaemia might be a challenge to the flash GM system . Additionally, during acute exercise accompanied by hypoglycaemia, flash GM data indicated a MARD of 45.1%; hence, glucose values must be interpreted very cautiously.…”
Section: Discussioncontrasting
confidence: 99%
“…Freestyle Libre 1, Abbott, USA; Dexcom G4 Platinum, Dexcom, USA) CGM systems. [7][8][9] The performance of the flash GM system sensor was found to be accurate, with an overall mean absolute relative difference of approximately 13% under routine environmental conditions. 8 During acute glycaemic challenges such as physical exercise or following carbohydrate-rich meals and high doses of exogenous insulin, the interstitial glucose response may be further delayed.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Level of evidence was set according to the Memorandum of Understanding (MOU) between the European Association for the Study of Diabetes (EASD) and the writing group of this position statement. Levels of evidence are, thus, categorised as: (Ia) evidence from meta-analysis of randomised controlled trials; (Ib) evidence from at least one Aberer et al (2017a) [35] Giani et al (2018) [36] Moser et al (2019) [24] Moser et al (2019) [25] Aberer et al (2017b) [35] Bally et al (2016a) [37] Bally et al (2016b) [37] Breton et al (2017) [29] Larose et al (2019) [16] Li et al (2019) [27] Steineck et al (2019a) [17] Steineck et al (2019b) [17] Taleb et al (2016a) [28] Taleb et al (2016b) [28] Zaharieva et al (2019) [22] Aberer et al (2017c) [35] Biagi et al (2018a) [33] Biagi et al (2018b) [33] Gomez et al (2015a) [30] Gomez et al (2015b) [30] Jayawardene et al (2017a) [31] Jayawardene et al (2017b) [31] Moser et al (2016a) [18] Moser et al (2016b) [18] Moser et al (2016c) [18] Moser et al (2016d) [18] Moser et al (2016e) [18] Moser et al (2016f) [18] Moser et al (2019a) [34] Moser et al (2019b) [34] Taleb et al (2016c) [28] Taleb et al (2016d) [28] Zaharieva et al (2017a) [32] Zaharieva et al (2017b) […”
Section: Data Sources Searches and Study Selectionmentioning
confidence: 99%
“…In contrast to some trial data [6], RT-CGM was not related to a lower number of severe hypoglycaemic events. Accuracy in the hypoglycaemic range remains an important weakness of most RT-CGM devices, certainly in the past [21].…”
Section: Discussionmentioning
confidence: 99%